Prevalence and associated factors of neck, shoulder, and low-back pains among medical students at Jazan University, Saudi Arabia: A cross-sectional study - Yahya Hadi Dighriri; Murad Abdullah Akkur; Sara Abdullah Alharbi; Nabeel Ahmed Madkhali; Kholoud Ibrahim Matabi; Mohamed Salih Mahfouz (Journal of Family Medicine and Primary Care, 2019)
Background: Musculoskeletal pain (MSP) in the neck, shoulder, and lower back is common widespread among medical students. The objective of this research is to estimate the prevalence of neck, shoulder, and low-back pains and to explore factors associated with MSP among medical students at Jizan University in southwest of Saudi Arabia. Methods: A cross-sectional, self-administered questionnaire-based study was conducted among undergraduate medical students of Jazan University. A total of 440 students were selected by random sampling. Descriptive statistics, a Chi-squared test, and logistic regression were performed to examine the prevalence, associations, and predictors of MSP. Results: The overall prevalence of MSP was (53.5%; 95% CI: 49.2–58.4). Neck pain was reported by 197 (44.8%) in the week prior to the study and by 268 (60.9%) in the year prior to the survey. Regarding shoulder pain, it was reported by 231 (52.5%) in the week prior to the study and 175 (39.8%) in the year prior to the study. Regarding low-back pain, it was reported by 147 (33.4%) in the week prior to the study and 270 (61.4%) in the year prior to the study. Factors associated with the risk of MSP include history of trauma (OR = 2.70; 95% CI: 1.36–5.36 depressive symptoms (OR = 1.94; 95% CI: 1.03–3.66) and report of psychosomatic symptoms (OR = 2.98; 95% CI: 1.71–5.18). Conclusion: In conclusion, the proportion of medical students with MSP was very high. Factors associated with the increased risk of MSP include history of trauma, depressive, and psychosomatic symptoms. Intervention program may help improving the musculoskeletal health of the medical students and to hence their quality of life.